2020
DOI: 10.3390/biology9040068
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Signaling Induces Mitochondrial Dysfunction-Associated Autophagy and Senescence in Breast Cancer Cells

Abstract: Previous work has shown that although estrogen (E2) disrupts cellular iron metabolism and induces oxidative stress in breast and ovarian cancer cells, it fails to induce apoptosis. However, E2 treatment was reported to enhance the apoptotic effects of doxorubicin in cancer cells. This suggests that E2 can precipitate anti-growth effects that render cancer cells more susceptible to chemotherapy. To investigate such anti-growth non-apoptotic, effects of E2 in cancer cells, MDA-MB-231 and MCF-7 cells were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Researchers in UAE have investigated the apoptotic effects of various compounds on cancer cells. Researchers have found that these compounds induce apoptotic cell death in cancer cells, as evidenced by various markers such as MTT assay, DNA ladder formation, and induction of p53 protein [ [57] , [58] , [59] ]. The exploration of novel cancer therapeutics is of great significance in many nations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in UAE have investigated the apoptotic effects of various compounds on cancer cells. Researchers have found that these compounds induce apoptotic cell death in cancer cells, as evidenced by various markers such as MTT assay, DNA ladder formation, and induction of p53 protein [ [57] , [58] , [59] ]. The exploration of novel cancer therapeutics is of great significance in many nations.…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing high-frequency sound waves, ultrasound can enhance drug penetration into tumors, trigger drug release from delivery systems, and improve cellular uptake. UCR aims to optimize the therapeutic outcomes of doxorubicin and chemotherapy by exploring innovative drug delivery systems and ultrasound parameters [ 57 , [60] , [61] , [62] , [63] , [64] ]. The ultimate goal is to improve targeted drug delivery, enhance the efficacy of doxorubicin, and mitigate its side effects, thereby advancing cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data indicated the role of E2 in breast cancer senescence. Studies by Bajbouj et al (2020) showed that E2 treatment of MCF-7 and MDA-MB-231 breast cancer cells reduced expression of p53, increased expression of p21 and LC3, presence of senescence-associated heterochromatin foci and higher levels of SA-βgalactosidase activity [202].…”
Section: Hormonal Therapymentioning
confidence: 99%